Proposal for a participatory photovoice workshop based on social methodology and intersectionality - Vargas Sandoval, Yensi (2026)
This essay proposes photovoice workshops as a tool for understanding the voices and feelings of young people. The objective was to offer a participatory workshop model using photovoice as a means not only to gather the perspectives of young people but also to enhance the pedagogical actions developed in schools as an opportunity for educational equity. Reflections were presented on social methodology and intersectionality as the theoretical and methodological foundation for the development of the workshops and for the subsequent analysis of the collected results. Argumentatively, it was argued that social methodology seeks greater reflection and involvement among those participating in pedagogical, research, outreach, or social action processes. Intersectionality was incorporated as a perspective that allows for addressing social reality by considering the multiplicity of factors or dimensions present within it. Furthermore, a photovoice workshop proposal was offered as a methodological option to amplify the voices of young people in the analysis of the complex reality experienced in schools. It was concluded that this strategy not only contributes to information gathering but also fosters the creation of educational spaces based on dialogue, mutual respect, and horizontal relationships. Finally, this initiative aims to generate narratives that strengthen community agency and contribute to social transformation, acknowledging the multiple dimensions of identity and inequality experienced by the participants.